Brain atrophy coupled to cognitive decline 3 years after stroke: Novel insights into the role of vascular risk factors in the development of Alzheimer's disease and neurodegeneration. (7th December 2020) - Brodtmann, Amy; Werden, Emilio; Khlif, Mohamed Salah; Bird, Laura J; Bradshaw, Jennifer; Egorova, Natalia; Restrepo, Carolina; Churilov, Leonid; Cumming, Toby
Abstract: Background: Cardiovascular risk factors and stroke are associated with increased risk of all‐cause dementia. More than one third of stroke patients will develop dementia, but mechanisms are unclear. Vascular brain burden from accumulated risk factors may contribute to cognitive impairment at the time of stroke, with the stroke being yet another manifestation of vascular disease. We examined total brain volume (TBV) and hippocampal volume (HV) in a group of stroke patients 3 years after their clinical event. We compared those who were cognitively impaired (CI) at 3 months after stroke to those who were cognitively normal (CN). We hypothesized that CI patients would exhibit greater total brain volume loss over the ensuing 3 years than those with normal cognition. Method: The Cognition And Neocortical Volume After Stroke (CANVAS) study is an observational cohort study of 135 patients with ischemic stroke examining brain volume and cognition over 3 years. All ischemic stroke types and etiologies were included. A history of cognitive impairment was an exclusion criterion. Participants were tested at baseline (within 6 weeks of stroke), 3 months, 1 year and 3 years after stroke. Total brain and hippocampal volume and neuropsychological testing were performed at each time‐point with the primary comparison being brain volume change between 3 months and 3 years. Only participants with usable MRI scans were included in this analysis (n=92). Clinical dementia panels were convened to produce consensus reports for CN, CI, or dementia. Result: At 3‐months post‐stroke, 67 patients (67.4 years, 15 women) were cognitively normal and 25 were cognitively impaired (74.7 years, 11 women); none had dementia. Total brain volume decline was greater in the CI group (M = 30.67 cm 3 n = 25) relative to the CN group (M = 19.63 cm 3 ; SD = 13.84 cm 3 ; n = 67). Hippocampal volume change between 3‐months and 3‐years was comparable in both groups. Conclusion: Total brain volume decline is greater over 3 years in stroke patients who have cognitive impairment at 3‐months post‐stroke. Hippocampal volume loss was not significantly associated with cognitive decline. Cognitive impairment at 3 months is associated with accelerated neurodegeneration in people with stroke.